Analisis Kepemimpinan Dan Kompensasi Kerja Terhadap Produktivitas Kerja Guru Pada SMA Negeri 1 Budong-Budong Kecamatan Budong-Budong Kabupaten Mamuju Tengah - salla, fuji inzani; Ameria, Riska; Ramli S, Ramli S (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
Education has a very strategic role in educating the life of the nation and is needed to improve the quality of the nation as a whole. An important factor that directly influences the educational process is the human resource factor, more specifically the educators or teachers. Teachers have an important role in the implementation of education at the education unit level, therefore, they are directed to become professionals based on the goal of increasing the quality of educational output. The purpose of this study was to determine the effect of Leadership and Work Compensation on Teacher Work Productivity at SMA Negeri 1 Budong-Budong, Budong-Budong District, Central Mamuju Regency. The population in this study were all 34 teachers at SMA Negeri 1 Budong-Budong, Budong-Budong District, Central Mamuju Regency. Because the population is relatively small, the sampling technique uses saturation sampling, in which all members of the population are used as respondents. The data collection technique uses a questionnaire. The data analysis method used is multiple linear regression analysis with the help of the SPSS program. The results showed that leadership and work compensation had a significant effect on teacher work productivity at SMA Negeri 1 Budong-Budong, Budong-Budong District, Central Mamuju Regency.